General practice ethnicity data: evaluation of a tool - Neuwelt P; Crengle S; Cormack D; McLeod M; Bramley D (CSIRO Publishing, 2014)
INTRODUCTION: There is evidence that the collection of ethnicity data in New Zealand primary care is variable and that data recording in practices does not always align with the procedures outlined in the Ethnicity Data Protocols for the Health and Disability Sector. In 2010, The Ministry of Health funded the development of a tool to audit the collection of ethnicity data in primary care. The aim of this study was to pilot the Ethnicity Data Audit Tool (EAT) in general practice. The goal was to evaluate the tool and identify recommendations for its improvement. METHODS: Eight general practices in the Waitemata District Health Board region participated in the EAT pilot. Feedback about the pilot process was gathered by questionnaires and interviews, to gain an understanding of practices' experiences in using the tool. Questionnaire and interview data were analysed using a simple analytical framework and a general inductive method. FINDINGS: General practice receptionists, practice managers and general practitioners participated in the pilot. Participants found the pilot process challenging but enlightening. The majority felt that the EAT was a useful quality improvement tool for handling patient ethnicity data. Larger practices were the most positive about the tool. CONCLUSION: The findings suggest that, with minor improvements to the toolkit, the EAT has the potential to lead to significant improvements in the quality of ethnicity data collection and recording in New Zealand general practices. Other system-level factors also need to be addressed.